Feeding Preference of Papilio memnon Linnaeus, 1758 (Lepidoptera) Larvae on Host Plants Citrus aurantifolia and Citrus hystrix (Rutaceae) - Zulnawati, Asih; Dahelmi, Dahelmi; Rahayu, Resti (Metamorfosa: Journal of Biological Sciences, 2018)
This research aimed to investigate the food preference of the Papilio memnon L. larvae on two host plants. This study was conducted by two choice food preference test combination of leaves Citrus aurantifolia Chrism. and Citrus hystrix DC. The result of this study showed that the third instar of P. memnon L. larva significant preferential feeding (P<0.05), while the fourth and fifth instar shown that no significant feeding preference beetwen host plants. Nitrogen and water content of leaves were higher on C. aurantifolia (0.212 % and 70.368%) than C. hystrix (0.04% dan 64.027%). While carbohydrate content was higher on C. hystrix (22.167%) than C.aurantifolia (31.097%).